2016
DOI: 10.1016/j.stem.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-Based Differential Single-Cell Analysis of the Niche to Identify Stem/Progenitor Cell Regulators

Abstract: SUMMARY Physiological stem cell function is regulated by secreted factors produced by niche cells. In this study, we describe an unbiased approach based on differential single-cell gene expression analysis of mesenchymal osteolineage cells close to and further removed from hematopoietic stem/progenitor cells to identify candidate niche factors. Mesenchymal cells displayed distinct molecular profiles based on their relative location. Amongst the genes which were preferentially expressed in proximal cells, we fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 43 publications
4
128
0
Order By: Relevance
“…and perivascular stromal cells, like CAR cells, (9,(14)(15)(16), and by cells that mediate the reconstitution of hematopoiesis after transplantation, like OSL cells (3,17,18). Del-1 promotes steady-state myelopoiesis.…”
Section: Cd51mentioning
confidence: 99%
See 3 more Smart Citations
“…and perivascular stromal cells, like CAR cells, (9,(14)(15)(16), and by cells that mediate the reconstitution of hematopoiesis after transplantation, like OSL cells (3,17,18). Del-1 promotes steady-state myelopoiesis.…”
Section: Cd51mentioning
confidence: 99%
“…Analysis of BM revealed that this difference was due to impaired reconstitution of myelo- of hematopoietic progenitors, particularly LT-HSCs, toward the myeloid lineage. After transplantation, hematopoietic progenitor cells localize in proximity to blood vessels at the endosteal area of the BM (3,17,18,39), which could be attributed to irradiation-induced disruption of sinusoids, though not of endosteal arterioles (3). The expression of Del-1 in the peri-arteriolar region and by OSL cells, which also contribute to the restoration of hematopoiesis after transplantation, prompted us to further investigate in more detail how Del-1 supports the regeneration of myelopoiesis.…”
Section: Cd51mentioning
confidence: 99%
See 2 more Smart Citations
“…These include CXCL-12, angiopoietin-1, stem cell factor (SCF), jagged-1, and thrombopoietin [56]. Recent work has taken this a step further using single cell analysis to define populations in close proximity to HSCs [57]. Cells within short distances of HSPCs had upregulation of cell surface proteins Vcam1, Adam9, and Amot as well as immune response genes Map3K14, CXCL12, and IL-18.…”
Section: Lscs Crosstalk With the Microenvironmentmentioning
confidence: 99%